Fantastic future - Goldsmith, Mike; Postgate, Daniel (New York : Scholastic, 2004)
In 30 years' time will you be holidaying on the moon? In 100 years' time could you genetically engineer your own pet? In 1000 years' time will you travel through space in an anti-matter-drive spaceship? This eye-opening guide predicts the future with a time-travelling trip through, well, time...Inside, visit vast skyscraper cities, make friends with robots and cyborgs, colonize far distant galaxies, and watch the very last star go out at the end of the universe. PLUS Read the Tomorrow's Times news reports from the future, discover how to terraform a desert planet and how to create a virtual you. If you want to be in the know, get The Knowledge
Keywords: future -- Non-fiction